2007
DOI: 10.1152/ajpcell.00106.2007
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory epithelia exhibit progressive functional and morphological defects in CF mice

Abstract: In normal nasal epithelium, the olfactory receptor neurons (ORNs) are continuously replaced through the differentiation of progenitor cells. The olfactory epithelium (OE) of the cystic fibrosis (CF) mouse appears normal at birth, yet by 6 mo of age, a marked dysmorphology of sustentacular cells and a dramatic reduction in olfactory receptor neurons are evident. Electroolfactograms revealed that the odor-evoked response in 30-day-old CF mice was reduced approximately 45%; in older CF mice, a approximately 70% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 57 publications
5
28
0
Order By: Relevance
“…We demonstrate herein that CFTR protein is present in non-neuronal cells of the mouse OE and VNO-SE as of E14 and E16, respectively, up to sexual maturity as well as in duct cells of vomeronasal glands. These findings are supported by previous morphological and biochemical data (Rochelle et al, 2000;Grubb et al, 2007) showing the presence of CFTR mRNA in the OE of adult mice, probably in OE sustentacular cells. In the human, CFTR is expressed in epithelia from before the start of the second trimester of development and it appears to be developmentally regulated in both human and sheep lung epithelium (Trezise et al, 1993;Tebutt et al, 1995;BroackesCarter et al, 2002).…”
Section: Cftrsupporting
confidence: 89%
See 1 more Smart Citation
“…We demonstrate herein that CFTR protein is present in non-neuronal cells of the mouse OE and VNO-SE as of E14 and E16, respectively, up to sexual maturity as well as in duct cells of vomeronasal glands. These findings are supported by previous morphological and biochemical data (Rochelle et al, 2000;Grubb et al, 2007) showing the presence of CFTR mRNA in the OE of adult mice, probably in OE sustentacular cells. In the human, CFTR is expressed in epithelia from before the start of the second trimester of development and it appears to be developmentally regulated in both human and sheep lung epithelium (Trezise et al, 1993;Tebutt et al, 1995;BroackesCarter et al, 2002).…”
Section: Cftrsupporting
confidence: 89%
“…The sustentacular cells are thought to play no role in stimulus detection; however, they are involved in, e.g., K + transport (Vogalis et al, 2005) and maintenance of water/salt balance in the NML (Menco et al, 1998;Rochelle et al, 2000) that can contribute to the equilibrium of the perireceptor environment. More recently, epithelial regulatory, secretory, and transport factors have been hypothesized to play a role in chemoreception: the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) and the aquaporins (AQPs) have been involved in olfaction (Ablimit et al, 2006;Grubb et al, 2007), and the Clara cell secretory protein 26 (CC26), a member of the cellular antioxidant system, has been involved in taste (Merigo et al, 2008). The epithelial transporters (CFTR and AQPs) are probably collaborating to regulation of the water and ionic environment at the chemoreceptor surface as well as the intercellular space; CC26 is conceivably involved in maintaining of the proper redox equilibrium in the epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…In its physiological role, ANO 1 seems to complement the action of the cystic fibrosis transmembrane conductance regulator (CFTR) protein, which is a cAMP-activated Cl − channel. CFTR plays a crucial role in maintaining the salt and water balance of mucosal secretions and is widely expressed in the nasal epithelia (Grubb et al 2007;Rochelle et al 2000). A notable exception is the Bowman's gland (Merigo et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, we have observed that the olfactory epithelia in CF mice undergo a severe and progressive degeneration, 42 and that isolated CF olfactory epithelia exhibit a much higher rate of Na + absorption than isolated CF respiratory epithelia (unpublished observation). Nasal PD measurements at different levels of the nasal cavity (olfactory or respiratory) have been shown to generate similar responses; 43 however, because the surface of the nasal epithelia is connected by the overlaying fluid, it is not clear that nasal PD measurements can be used to determine the contribution of specific cell types to the overall PD.…”
Section: Cftr Expression In Murine Ciliated Cells Le Ostrowski Et Almentioning
confidence: 91%